Direct sequencing of human gut virome fractions obtained by flow cytometry - Džunková, Mária; D'Auria, Giuseppe; Moya, Andrés (Frontiers in Microbiology, 2015)
The sequence assembly of the human gut virome encounters several difficulties. A high proportion of human and bacterial matches is detected in purified viral samples. Viral DNA extraction results in a low DNA concentration, which does not reach the minimal limit required for sequencing library preparation. Therefore, the viromes are usually enriched by whole genome amplification, which is, however, prone to the development of chimeras and amplification bias. In addition, as there is a very wide diversity of gut viral species, very extensive sequencing efforts must be made for the assembling of whole viral genomes. We present an approach to improve human gut virome assembly by employing a more precise preparation of a viral sample before sequencing. Particles present in a virome previously filtered through 0.2 µm pores were further divided into groups in accordance with their size and DNA content by fluorescence activated cell sorting (FACS). One selected viral fraction was sequenced excluding the whole genome amplification step, so that unbiased sequences with high reliability were obtained. The DNA extracted from the 314 viral particles of the selected fraction was assembled into 34 contigs longer than 1,000 bp. This represents an increase to the number of assembled long contigs per sequenced Gb in comparison with other studies where non-fractioned viromes are sequenced. Seven of these contigs contained open reading frames (ORFs) with explicit matches to proteins related to bacteriophages. The remaining contigs also possessed uncharacterized ORFs with bacteriophage-related domains. When the particles that are present in the filtered viromes are sorted into smaller groups by FACS, large pieces of viral genomes can be recovered easily. This approach has several advantages over the conventional sequencing of non-fractioned viromes: non-viral contamination is reduced and the sequencing efforts required for viral assembly are minimised.